Presencia de Comadrejita Trompuda (Rhyncholestes raphanurus) en la Cordillera de la Costa Valdiviana, Chile - Vásquez-Ibarra, Viviana; Cortés, Esteban; Stillfried, Laura; Ovando, Erwin; González, Danilo; Contreras, Patricio; Silva-Rodriguez, Eduardo (BOSQUE, 2023)
In this work, we report new records of the Chilean shrew opossum (Rhyncholestes raphanurus), one of the least known mammals of the South American temperate rainforests. Using camera traps, we detected Chilean shrew opossum at 17 sites, located in two protected areas of Los Ríos region, Chile. The records were obtained in evergreen and alerce forests, and in eucalyptus plantations and show markedly nocturnal activity. These records represent a significant increase in the number of localities where the presence of this species has been confirmed.